MEDIA PEMBELAJARAN BERBASIS GAME EDUCAPLAY UNTUK MENINGKATKAN MINAT BELAJAR PADA MATA PELAJARAN PANCASILA SD - Ni Komang Ayu Suandenik; I Made Tegeh; I Wayan Ardana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Students interest in learning the subject of Pancasila in elementary school remains relatively low due to conventional and insufficiently interactive teaching methods. This study aims to develop the Educaplay game-based learning medium and analyze its validity, practicality, and effectiveness in increasing students’ interest in learning. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 2 media experts, 2 content experts, 2 teachers, 6 students in the small-group pilot test, and 33 fourth-grade students at SDN Sekaan in the effectiveness test. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed using descriptive quantitative and qualitative methods. The research results indicate that the developed media has a very acceptable level of validity with an average score of 3.73 (media experts) and 3.70 (content experts), as well as very acceptable practicality with an average score of 3.60 (teachers) and 3.58 (students). The results of the effectiveness test showed a significant increase in learning interest with a Sig. (2-tailed) value of 0.000 (<0.05). Thus, the Educaplay-based learning media is deemed valid, practical, and effective in increasing students’ learning interest in the Pancasila subject in elementary school. ABSTRAK Minat belajar siswa pada mata pelajaran Pancasila di sekolah dasar masih tergolong rendah akibat pembelajaran yang bersifat konvensional dan kurang interaktif. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis game Educaplay serta menganalisis tingkat validitas, kepraktisan, dan efektivitasnya dalam meningkatkan minat belajar siswa. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Subjek penelitian terdiri atas 2 ahli media, 2 ahli materi, 2 guru, 6 siswa pada uji kelompok kecil, serta 33 siswa kelas IV SDN Sekaan pada uji efektivitas. Data dikumpulkan melalui observasi, wawancara, angket, dan dokumentasi, kemudian dianalisis secara deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa media yang dikembangkan memiliki tingkat validitas sangat layak dengan nilai rata-rata 3,73 (ahli media) dan 3,70 (ahli materi), serta kepraktisan sangat layak dengan nilai rata-rata 3,60 (guru) dan 3,58 (siswa). Hasil uji efektivitas menunjukkan adanya peningkatan minat belajar yang signifikan dengan nilai Sig. (2-tailed) sebesar 0,000 (<0,05). Dengan demikian, media pembelajaran berbasis Educaplay dinyatakan valid, praktis, dan efektif dalam meningkatkan minat belajar siswa pada mata pelajaran Pancasila di sekolah dasar.